The potential of honey production as business development alternative for village owned enterprises and MSMEs - Kamadie Sumanda Syafies; Ernie Hendrawaty; Lidya Ayuni Putri; Sari Indah Oktanti Sembiring; Siti Normah binti Awang Tuah; Zunaidah bin Abdul Hasan (Journal of Community Service and Empowerment, 2023)
Community service is a process of self-empowerment for the benefit of society. This service is based on problems that occur in the community that the potential of existing honey has not been optimized to become a superior product. In addition, honey-producing bee farmers only produce honey in one product, namely real honey. Gradually, this product is certainly less attractive to consumers even though honey production keeps continue. Therefore, it is important to explore new business development alternatives so that farmers can receive more benefits from honey bee cultivation. In this community service activity, the team collaborated with Universiti Teknologi Mara (UiTM) Cawangan Melaka, Malaysia with the title Business Development: Potential for Honey Production as an Alternative for Business Development. The methods used in this service are demonstrations and lectures to the participants. The results of community service carried out in Way Kalam Village, Penengahan District, South Lampung Regency, Lampung Province with speakers from UiTM have proven to be able to increase the ability of bee farmers to carry out honey production to marketing and increase the potential income generated from selling honey.